THE INFLUENCE OF CONFLICTS TO MIGUEL’S MAIN CHARACTER DEVELOPMENT IN “COCO” MOVIE - B, Nuralim; Halim, Abdul (Journal of English Literature and Linguistic Studies, 2023)
This research is a descriptive qualitative research that analyzes the conflicts face by Miguel and his personality development. The aims of this study are: (1) To find out what are the conflicts faced by Miguel’s main character in Coco movie by Lee Unkrich and Adrian Molina; (2) To find out how do conflicts affect Miguel’s personality development; (3) To find out how did Miguel solves his conflicts. The data for this study were obtained by watching the movie. Analysis of the data used an interactive analysis model which includes data reduction, data display, and conclusions (Huberman & Saldana, 2014). Based on the research results, the writer found 2 types of conflicts faced by the main character that occurred in Coco movie: internal conflict and external conflict. Internal conflicts which consist of: bad luck, admiration, fear, anger, confuse, panic, nervous; External conflicts which consist of: character vs. society and character vs. supernatural. Miguel was born in a family that hates music. He wants to become a musician but his family always banned him. This problem makes him travelled to the land of the dead to find out the truth of his family. At first, Miguel is described as an ambitious, selfish, stubborn, fanatical boy. Due to his experiences of particular changes in the land of the dead, he turns into an obedient, wise, unselfish and regretful boy.